A Criticism and Review of the Book “Public Policy” - Morteza Noormohammadi; Amir Lotfi; Zahra Lotfi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Public Policy, written by Pierre Muller, is one of the first books on public policy that has been translated and published in Iran. Known as the science of a state in action and analyzing the public policies and also as an academic discipline, public policy has attracted the attention of experts in Iran since more than a decade ago, and it is now being taught in a limited number of universities. Regarding the structure of policymaking and decision-making in France, the writer of this book has attempted to make the readers familiar with the important and fundamental concepts in the field of public policy and propose an approach for the study of public policy to the interested readers and students. After providing an initial introduction to the concept of public policy, as a new discipline in Iran, the book chapters are introduced and discussed respectively. The review and critiques of the book translation are included in this article.